The Use of Biological Meshes in Diaphragmatic Defects – An Evidence-Based Review of the Literature - Antoniou, Stavros A.; Pointner, Rudolph; Granderath, Frank-Alexander; Köckerling, Ferdinand (Frontiers in Surgery, 2015)
The widespread use of meshes for hiatal hernia repair has emerged in the era of laparoscopic surgery, although sporadic cases of mesh augmentation of traumatic diaphragmatic rupture have been reported. The indications for biologic meshes in diaphragmatic repair are ill defined. This systematic review aims to investigate the available evidence on the role of biologic meshes in diaphragmatic rupture and hiatal hernia repair. Limited data from sporadic case reports and case series have demonstrated that repair of traumatic diaphragmatic rupture with biologic mesh is safe technique in both the acute or chronic setting. High level evidence demonstrates short-term benefits of biologic mesh augmentation in hiatal hernia repair over primary repair, although adequate long-term data are not currently available. Long-term follow-up data suggest no benefit of hiatal hernia repair using porcine small intestine submucosa over suture repair. The effectiveness of different biologic mesh materials on hernia recurrence requires further investigation.